Mapping Trends in Early Childhood Education Research in Support of SDG 4: A Bibliometric Analysis (2015–2025). - Kiki Irafa Candra; Rudiana Rudiana (Journal of Art and Creativity in Early Childhood Education, 2026)
Early Childhood Education (ECE) has been widely recognized as a fundamental pillar in achieving sustainable human development, particularly within the framework of Sustainable Development Goal 4 (SDG 4), which emphasizes inclusive and equitable quality education for all. Despite the growing number of scholarly publications in this field, a comprehensive understanding of research trends, thematic evolution, and global collaboration patterns remains limited. This study aims to map the development of ECE research in supporting SDG 4 through a bibliometric analysis of publications indexed in the Scopus database from 2015 to 2025. A total of 661 articles and review papers were selected based on predefined inclusion and exclusion criteria. Data were analyzed using Biblioshiny (Bibliometrix R-package) and VOSviewer to examine publication trends, thematic structures, core journals, and international collaborations. The findings reveal that research in ECE is dominated by well-established themes such as “early childhood education” and “human development,” which function as motor themes with high centrality and density. Core journals play a significant role in shaping the intellectual structure of the field, reflecting a concentration of knowledge dissemination. However, the results also indicate a lack of emerging and innovative themes, particularly in areas such as digital integration, inclusive education, and community-based approaches. Furthermore, global research collaboration is largely dominated by developed countries, especially the United States, Australia, and the United Kingdom, while contributions from developing countries remain limited. This study highlights the need for greater diversification of research themes and more inclusive global collaboration to strengthen the contribution of ECE research toward achieving SDG 4. The findings provide valuable insights for researchers, policymakers, and practitioners in identifying research gaps and future directions in early childhood education. Keywords: Early Childhood Education; SDG 4; Bibliometric Analysis; Research Trends; Thematic Mapping; Global Collaboration; Quality Education